NETRALITAS POLITIK KIAI DALAM PERSPEKTIF TEORI INTERAKSI SIMBOLIK - Nurma Yuwita; Ahmad Aminuddin; Gatut Setiadi (Jurnal Dakwah Risalah, 2019)
The researcher examines the neutrality of the Kiai in the political year due to the existence of one of the candidates for the vice president who participated in the 2019 election is a great Ulama. The political stage not only presents the political maneuver of political figures and parties, but also the role of the Kiai who also took part in the democratic party. One of the kiai who has neutrality in politics is K.H. Sholeh Bahruddin, better known by the name of Kiai Sholeh. The purpose of this study is to analyze the neutrality of the kiai’s politics in the perspective of symbolic interaction theory. The methodology used in this research is descriptive qualitative. This research uses Symbolic Interactionism theory for its analysis. The result of the analysis shows that the neutrality of the Kiai is a solution to create peaceful election. Kiai Sholeh made several efforts to realize a peaceful election by: Firstly, Kiai Sholeh committed to uphold the integrity and sovereignty of the Republic of Indonesia based on Pancasila; Secondly, Kiai Sholeh supported the democratic system and the process of democratization as a political mechanism of the state; and finally, prioritizing peace, tolerance, and togetherness amid differences in political choices.